Ion Substitution Behavior and Chromatographic Study of “Ya’an Green” Seal Stone - Yicong Sun; Yigeng Wang; Zixuan Wang; Zheng Zhang; Mingming Xie; Zhuchun Peng; Bin Meng; Siqi Yang; Endong Zu (Crystals)
In recent years, domestic research on the ion substitution behavior and chromaticity of the mineral composition of “Ya’an Green” remains insufficient, while there is almost no relevant research on “Ya’an Green” abroad. In this study, X-ray powder diffraction (XRD), electron probe microanalysis (EPMA), infrared spectroscopy (IR), ultraviolet–visible spectroscopy (UV-Vis), and colorimetry were employed. The results indicate that the green and yellow matrices of “Ya’an Green” are primarily composed of muscovite, with rutile also present in the yellow matrix. In contrast, the white–green samples are mainly composed of quartz, with muscovite as a secondary mineral. Additionally, it was observed that the (004) crystal plane of muscovite exhibits a peak shift to lower 2θ angles, attributed to the substitution of Al3+ by ions with larger radii, such as Ba2+, Cr3+, and Fe2+, leading to an increase in unit cell parameters and a consequent shift in the peak to lower wavenumbers. The main elements of “Ya’an Green” are Al, Si, and K, with minor elements including Na, Fe, and Cr. Furthermore, Mg2+, Ca2+, Ti4+, Cr3+, and Fe2+ in the samples can substitute for Al3+ through isomorphic substitution. The infrared spectrum of muscovite in the ‘Ya’an Green’ sample shows three typical absorption peaks, 422 cm−1 and 513 cm−1 caused by Si-O bending vibration, 697 cm−1 and 837 cm−1 caused by Si-O-Al vibration, 948 cm−1 caused by O-H bending vibration, and 3647 cm−1 caused by O-H stretching vibration. The peak at 837 cm−1 exhibits varying degrees of shift due to the substitution of Al3+ by ions with larger radii. The ultraviolet–visible spectra display two broad absorption bands at 422 nm and 615 nm, which are caused by Cr3+ transition, indicating that Cr is the chromogenic element responsible for the green color. A correlation was observed between the Cr3+ content and the hue angle h in “Ya’an Green” samples: the higher the Cr3+ content, the closer the hue angle is to 136°, resulting in a darker green color, while lower Cr3+ content leads to a deviation from the dark green hue. This study establishes for the first time the correlation between the mineral composition of ‘Ya’an Green’ and its chromatic parameters and explores the linear relationship between its color and the number of color-causing elements and elemental substitution, which provide data support and theoretical models for the study of the color of seal stones.